Exploring a communication curriculum through a focus on social accountability: A case study at a South African medical school - Margaret G. Matthews; Jacqueline M. Van Wyk (AOSIS, 2018)
Background: Good communication is integral to social accountability, and training is included in medical curricula internationally. In KwaZulu-Natal, training is conducted in English, in spite of most public sector patients being mother tongue isiZulu speakers. Communication challenges with patients are common, but good communication and African language teaching are not emphasised in teaching. Aim: This study explored communication training and how it related to social accountability at a single institution in KwaZulu-Natal. Setting: This exploratory, qualitative case study design at the medical school explored participants' perceptions about communication and social accountability and reviewed relevant educational documentation for evidence. Methods: Purposive sampling was used to select medical students, educators and stakeholders from the educational and service platforms. Focus group discussions and semi-structured interviews were conducted. The data were thematically analysed with reference to Boelen's social obligation scale for medical schools. Results: Good communication was valued, but often poorly role-modelled. Participants agreed that communication and isiZulu teaching were insufficiently supported to respond adequately to the needs of local communities. Social accountability was not well understood by students, while medical school educators and other stakeholders indicated that, despite aspirations, this goal had not yet been achieved. Conclusions: Learning isiZulu language and culture in an integrated manner in both preclinical and clinical phases would improve communication with patients, contribute to socially responsive health care, and better address health care needs. Incorporating a social accountability framework in curriculum review would highlight the importance of measuring health outcomes and community impacts, and so enhance the educational mission of the medical school.